Photoelectrical analysis of n-TiO₂/p-CdTe heterojunction solar cells - Brus, V.V.; Maryanchuk, P.D.; Parfenyuk, O.A.; Vakhnyak, N.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
Photoelectrical properties of n-TiO₂/p-CdTe heterojunction solar cells were investigated under different light conditions, taking into account the presence of series and shunt resistances. The effect of light dependent dominating charge transport mechanism based on tunnel-recombination processes at the TiO₂/CdTe heterojunction interface was taken into consideration. The width W of the space charge region of the CdTe-pTiO₂-n solar cells and consequently the concentration of uncompensated acceptors NA - ND were determined using the open-circuit method.